Search for third-generation scalar leptoquarks and heavy right-handed neutrinos in final states with two tau leptons and two jets in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2017)
A search is performed for third-generation scalar leptoquarks and heavy right-handed neutrinos in events containing one electron or muon, one hadronically decaying tau lepton, and at least two jets, using a root s = 13 TeV pp collision data sample corresponding to an integrated luminosity of 12: 9 fb(-1) collected with the CMS detector at the LHC in 2016. The number of observed events is found to be in agreement with the standard model prediction. A limit is set at 95% confidence level on the product of the leptoquark pair production cross section and beta(2), where beta is the branching fraction of leptoquark decay to a tau lepton and a bottom quark. Assuming beta = 1, third-generation leptoquarks with masses below 850 GeV are excluded at 95% confidence level. An additional search based on the same event topology involves heavy right-handed neutrinos, N-R, and right-handed W bosons, W-R, arising in a left-right symmetric extension of the standard model. In this search, W-R bosons are assumed to decay to a tau lepton and N-R followed by the decay of the N-R to a tau lepton and an off-shell W-R boson. Assuming the mass of the right-handed neutrino to be half of the mass of the right-handed W boson, W-R boson masses below 2.9 TeV are excluded at 95% confidence level. These results improve on the limits from previous searches for third-generation leptoquarks and heavy right-handed neutrinos with tau leptons in the final state.